SAE Technical Paper Series 2014
DOI: 10.4271/2014-01-2634
|View full text |Cite
|
Sign up to set email alerts
|

Smoke Reduction Effects by Post Injection for Various Injection Parameters and Combustion Chamber Shapes in a Diesel Engine

Abstract: A series of experiments using a single-cylinder direct injection diesel engine was conducted to investigate the smoke reduction effect of post injection while varying numerous parameters: the post-injection quantity, post-injection timing, injection pressure, main-injection timing, intake pressure, number of injection nozzle orifices, and combustion chamber shape. The experiments were performed under a fixed NOx emission condition by selecting the total injection quantities needed to obtain the predetermined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The experimental system and measurement methods used in this study were essentially the same as those reported in the previous study [22]. The test engine was a water-cooled single-cylinder four-stroke-cycle direct-injection diesel engine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental system and measurement methods used in this study were essentially the same as those reported in the previous study [22]. The test engine was a water-cooled single-cylinder four-stroke-cycle direct-injection diesel engine.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study [22], an experimental study was performed using a small-bore single-cylinder diesel engine by changing the post-injection timing for various post-injection quantities, injection pressures, main-injection timings, intake pressures, numbers of injection nozzle orifices, and combustion chamber shapes. The results indicated that close post injection provides lower smoke emission for the combination of a reentrant combustion chamber and seven-hole nozzle.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the extent of interaction between a post-jet and the main combustion remnants will also depend on these designs. Horibe et al [12] have investigated post-injection strategies using several combinations of piston bowl and injector nozzle geometries. It was found that the soot reduction response to post-injection timing flattens when the number of nozzle holes is increased.…”
Section: Introductionmentioning
confidence: 99%